IMPLEMENTATION OF E-DIDACTICS IN COMPLEX ANALYSIS EXAMS: ITS IMPACT ON STUDENTS' COGNITIVE ABILITIES, RESILIENCE, AND SELF-AWARENESS - Hamdan Sugilar; Juariah Juariah; Jarnawi Afghani Dahlan (UIN Imam Bonjol Padang, 2026)
The implementation of e-didactics through the use of various digital tools and platforms in learning requires appropriate assessment techniques and student skills in using them to measure learning outcomes. This study aims to: (1) determine students' ability to solve Complex Analysis exam questions assisted by mathematical computer applications; (2) identify appropriate question formats to measure mathematical problem-solving abilities; and (3) measure the level of resilience and self-awareness of students during the exam. This study uses a qualitative descriptive approach. The researcher aims to explore the role of e-didactics assisted by the Learning Management System (LMS) and mathematical computer applications on the ability to solve analytical questions, resilience, and self-awareness of sixth-semester students of the Mathematics Education Study Program at a university in Bandung City. The context of this study is when students complete the Mid-Semester Exam (UTS) questions for the Complex Analysis course. The results of the study indicate that: (1) students' analytical abilities are in the sufficient category; (2) appropriate question formats to measure analytical abilities are multiple-choice and essay questions with analytical question types; and (3) the level of self-awareness and resilience of students during the application-assisted mid-term exam was also in the sufficient category. For further research, it is recommended that e-didactic studies not only focus on the evaluation stage, but also be reviewed from the perspective of the entire learning process.